2014
DOI: 10.1128/jb.01923-14
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Role of the RNA Chaperone Protein Hfq in the Human Pathogen Clostridium difficile

Abstract: cClostridium difficile is an emergent human pathogen and the most common cause of nosocomial diarrhea. Our recent data strongly suggest the importance of RNA-based mechanisms for the control of gene expression in C. difficile. In an effort to understand the function of the RNA chaperone protein Hfq, we constructed and characterized an Hfq-depleted strain in C. difficile. Hfq depletion led to a growth defect, morphological changes, an increased sensitivity to stresses, and a better ability to sporulate and to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
114
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(126 citation statements)
references
References 103 publications
9
114
0
Order By: Relevance
“…2A). Low sporulation frequencies in C. difficile have been observed in other studies (1,63,64); however, the percentage of spore formation reported is widely variable, depending on the strain, medium, and methods used to enumerate spores (63). As shown in Fig.…”
Section: Identification Of Opp and App Transporters In C Difficilementioning
confidence: 83%
“…2A). Low sporulation frequencies in C. difficile have been observed in other studies (1,63,64); however, the percentage of spore formation reported is widely variable, depending on the strain, medium, and methods used to enumerate spores (63). As shown in Fig.…”
Section: Identification Of Opp and App Transporters In C Difficilementioning
confidence: 83%
“…We failed to inactivate the gene encoding the PatB/MalY enzyme, probably because of its essentiality for C. difficile (51). Thus, to evaluate whether PatB/MalY is a cysteine desulfhydrase, we constructed a PatB/MalY-depleted strain using an antisense strategy (36,52). Compared to the strain carrying the control plasmid (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hfq contributes to stress tolerance and pathogenicity in Listeria monocytogenes (22), Clostridium difficile (23) and other Gram positive bacteria (24). By contrast, deletion of Hfq from Bacillus subtilis and Staphylococcus aureus has almost no detectable phenotype (25, 26).…”
mentioning
confidence: 99%